대학 교양과목을 통한 지역학에 대한 수강생들의 인식 －역사문화 체험을 중심으로 한 안동학 사례 - 김용남 (교양교육연구, 14(3), 2020)
본 연구는 대학 교양과목을 통한 지역학에 대한 수강생들의 인식을 안동학 사례를 중심으로 내러티브 연구를 통해 알아보았다. 연구방법은 본 연구자와 함께 A 대학교에서 지역학(안동학) 수강생을 대상으로 15주 학습과정 속 내러티브 인터뷰를 통해 진행하였다. 연구결과 수강생들은 안동학 수업을 통하여 지역정체성 확립이 지향되었으며, 지역의 다양한 문화적 욕구를 충족시킬 수 있었다. 또한, 정서적 교류를 촉진 시키고 교육 자체보다도 인간적 관계를 돈독하게 하였다. 이러한 친밀감을 통해 지역적 특성을 소유하고 지역사회에 대한 관심이 커지고 지역에 대한 소속감이 높아졌다. 다른 지역 학생들이 지역학 수업을 통하여 애착을 가지게 되었고 지역학의 대중화와 실용화에 관심을 가지는 것으로 확인되었다. 이러한 결과를 바탕으로 학생들이 각 지역의 다양한 지역 사회 활동가들과 소통 할 수 있는 장을 마련하고 다양하고 체계적인 지역 교육 프로그램들을 연구해야 한다. 향후 지역학이 이론적 논의나 학문적 연구로만 그치지 않고 지역 현장에서 도움이 되고 대중적으로 다가갈 수 있는 학문이기를 기대한다. This study examined the students' perceptions of regional studies through university liberal arts using a narrative study focusing on the cases in the Andong Study. The research method was conducted through a narrative interview in the 15-week learning process, targeting the students of the regional study (Andong Study) at University A, along with the researcher. As a result of the study, the students were oriented toward establishing a regional identity through the Andong Study classes, and were able to satisfy various cultural needs of the region. In addition, this study promoted emotional exchange among the students, and strengthened human relationships, rather than simply focusing on education itself. Through this intimacy, the students learned about certain regional characteristics, increased their interest in the local community, and raised their sense of belonging to the region. It was confirmed that students from other regions developed attachments through regional study classes and were interested in the popularization and practical use of regional studies. Based on these results, it will be necessary to prepare a place in which students can communicate with various community actors in their respective regions, and to study various and systematic regional educational programs. In the future, it is expected that regional studies will not only go beyond theoretical discussions and/or academic studies, but will also serve as helpful and popular approaches in the local field. KCI Citation Count: 1